Nostalgia proneness and empathy: Generality, underlying mechanism, and implications for prosocial behavior. Issue 3 (11th September 2019) - Juhl, Jacob; Wildschut, Tim; Sedikides, Constantine; Diebel, Tara; Cheung, Wing‐Yee; Vingerhoets, Ad J. J. M.
Abstract: Objective: Nostalgia is a sentimental longing for one's past. We examined the hypotheses (rooted in attachment theory and research) that nostalgia prone individuals, by virtue of their greater attachment security, are more empathic and enact more prosocial behavior. Method: In five studies, testing 1, 923 participants ( N range  = 132–823, 52.42% women, Agerange  = 8–90 years), we measured nostalgia proneness and affective empathy. Additionally, we measured cognitive empathy in Study 3, attachment security in Studies 4–5, and prosocial behavior in Study 5. Results: Nostalgia proneness was positively related to affective empathy among younger and older adults (Studies 1, 3–5) and among children (Study 2). This association was stronger for affective empathy than cognitive empathy (Study 3). Also, attachment security mediated the relation between nostalgia proneness and affective empathy (Studies 4–5). Finally, nostalgia prone individuals were more likely to engage in prosocial behavior, and this relation was serially mediated by attachment security and affective empathy (Study 5). Conclusion: The findings establish the empathic and prosocial character of nostalgia prone individuals, and clarify their personality profile.